STUDENT'S CONCEPT OF TECHNOLOGY AND BASIC COGNITION OF HISTORY OF TECHNOLOGY - KROPAC, Jiri; HAVELKA, Martin; SERAFIN, Cestmir (Trends in education, 2012)
One of the teacher's basic tasks in technical subjects is to create a student's objective concept of technology supported by balanced arguments for and against technical solutions. The paper focuses on the importance of history of technology cognition in order to create the student's concept of technology which is a part of his concept of the world. Lack of future teachers' knowledge of history of technology is also mentioned.
Keywords: technical education; concept of the world; concept of technology; history of technology.